AB0691 Oblique Views Have Advantages over Antero-Posterior View Radiographs in Assessing Sacroiliitis: An Imaging Study. (15th July 2016) - Hu, Z.; Zhang, P.; Qi, J.; Qiu, M.; Guo, X.; Gu, J.
Abstract : Background: Radiograph of antero-posterior (A-P) view of pelvis is usually used to diagnose sacroiliitis. Magnetic resonance imaging (MRI) can detect lesions early in the disease course before they can be seen on radiography. The severity of sacroiliitis may be different as detected by MRI or by A-P view X-ray. The oblique view of pelvis may provide additional information that makes it closer to the finding of MRI than A-P view X-ray. Objectives: To record lesions of sacroiliac joint (SIJ) seen on A-P view and oblique views radiographs and MRI in patients with axial Spondyloarthritis (SpA), and to analyze whether oblique views have advantages over A-P view radiographs in assessing sacroiliitis. Methods: Three readers blinded graded the sacroiliitis according to the modified New York criteria seen on A-P view, oblique views and MRI from 182 patients with axial SpA. We summarized the characteristics of scores assessed by three kinds of imaging methods and calculated the sensitivity, specificity, positive and negative likelihood ratio of A-P view and oblique views radiographs for diagnosing axial SpA with MRI as the gold-standard. Results: The total accuracy of oblique views was higher than that of A-P view in assessing sacroiliitis as referred to the data of MRI (82.8% vs. 71.6%, p<0.01). The agreements were higher between oblique views and MRI than that between A-P view and MRI in the SIJs graded ≤2, especially in patients with symptom duration less than 2 years (all p<0.01). But in the SIJs graded >2 and in patients with symptom duration more than 2 years, there were no differences using A-P view or oblique views to assess sacroiliitis (all p>0.05). Oblique views had high sensitivity, while A-P view had moderate sensitivity for diagnosing axial SpA in the SIJs graded ≤2. Conclusions: We recorded and analyzed the sacroiliitis assessed by A-P view, oblique views radiographs and MRI and found that oblique views had some advantages over A-P view radiographs in assessing sacroiliitis. References: van Gaalen FA, Bakker PA, de Hooge M, et al. Assessment of sacroiliitis by radiographs and MRI: where are we now? Curr Opin Rheumatol 2014;26:384–8. van Tubergen A, Weber U. Diagnosis and classification in spondyloarthritis: identifying a chameleon. Nat Rev Rheumatol 2012;8:253–61. Eshed I, Hermann KG. Novel imaging modalities in spondyloarthritis. Curr Opin Rheumatol 2015;27:333–42. Disclosure of Interest: None declared